Barriers to antiretroviral therapy initiation for HIV-positive children aged 2–18 months in Swaziland. Issue 2 (3rd April 2018) - Jolly, Pauline; Padilla, Luz A; Ahmed, Charisse; Harris, Chantal; Mthethwa, Nobuhle; Jha, Megha; Ba, Inessa; Styles, Amy; Hope, Sarah P; Brooks, Raina; Naluyinda-Kitabire, Florence; Mamba, Makhosini; et al.
Abstract : Although early antiretroviral therapy (ART) reduces HIV-related mortality in children by up to 75%, almost half of HIV-positive children younger than 1 year old in Swaziland do not initiate ART. This study was conducted to identify barriers to early ART initiation among HIV-positive infants. This was a case-control study among HIV-positive infants, aged 2 to 18 months, who either did not initiate ART (cases), or initiated ART (controls), during 18 months after testing. Multivariable logistic regression showed that infants who visited the clinic every month, or every 2 months, were 5.78 and 6.20 times more likely to initiate ART than those who visited less often (OR 5.78, 95% CI 1.82–18.33 and OR 6.20, 95% CI 1.30–29.60 respectively). Children who lived ≤30 and 31–60 minutes from the nearest clinic were 84% and 79% less likely respectively to initiate ART (OR 0.16, 95% CI 0.03–0.78 and OR 0.21, 95% CI 0.04–0.98) compared with those who lived more than 60 minutes away. Children who received immunisation after 6 months were 22.59 times more likely to initiate ART (OR 22.59, 95% CI 7.00–21.72) than those who did not. Infants of caregivers who had excellent or good relationships with their healthcare provider were 4.32 times more likely to initiate ART (OR 4.32, 95% CI 1.01–18.59) than those of caregivers who had average or poor relationships with healthcare providers. The significant predictors of ART initiation identified in this study should be regarded as priority areas for intervention among HIV-positive women in Swaziland.